Safety and efficacy of glued intraocular lens implantation in eyes with inadequate capsular support - Gonde, Payal P.; Aghadate, Sagar (International Journal of Research in Medical Sciences, 2020)
Background: Aim of the study was to analyze the postoperative visual outcomes, complication rate of fibrin glue-assisted, suture-less posterior chamber (PC) intraocular lens (IOL) implantation technique in eyes with inadequate capsule support at a tertiary eye care hospital. Methods: This is a retrospective, nonrandomized case series. This study analyzes 50 eyes which underwent PC-IOL implantation by fibrin glue-assisted, suture-less technique. All patients who had IOL implants by the fibrin glue-assisted PC-IOL technique from 2017 to 2019 were included in the study. Intra- and post-operative complications were analyzed. The postoperative best corrected visual acuity (BCVA) was evaluated and recorded at the end of 6 months. Results: Mean age of distribution are 42.94 years in glued IOL implantation. Among 50 cases 30 are males and 20 are females. There is significant difference in BCVA between preoperatively and postoperatively, p value for pre-operative to post-operative vision in glued intraocular lens group is <0.0001 i.e. there is definite improvement in vision in glued intraocular group. BCVA ≥6/24 was 18 (48%) in Glued IOL subjects. Conclusions: Glued IOL implantation is a feasible option in rehabilitating patients with aphakia without adequate capsular support.